Matrix of predictive values as a tool for management decision-making (Economics and region, 2018)
In the article the presented and demonstrated the author's proven development about the use of matrix of predictive values as a tool for management decision-making entities of the national economy, which was the main purpose of the study. To predict changes of integrated efficiency value, for example, resources with the use of proposed methodological approach, was tested computer program that take into account the mutual influences and makes possible to calculate the projected impact on the evaluation of integrated resource efficiency. On the base of this methodology put equal-weight influence of efficiency types (for example, used the economic, social and environmental efficiency types), influence of different-weight components (indicators) types of performance and assumptions, and suggested that the change of one of the indicators on a certain amount varies importance of integrated effectiveness.In addition, certain projections database take into account the relationship of individual input parameters and is a versatile tool for management decision-making in the presence of some of the resources and capabilities of the national economy.Using authoring matrix of predictive values considerably facilitates calculation procedures and perception of practical nature of forecasting economic, environmental and social efficiency of resource management at the enterprise level, region and country (countries), including in the context of harmonization with integration and globalization prospects for sustainable development and food security of Ukraine.
Keywords: management decision making; forecast; matrix; interdependent; national resources